Charge Breeder at GANIL: metal charge-bred elements. Issue 1 (1st April 2022) - Maunoury, L.; Dubois, M.; Damoy, S.; Bajeat, O.; Chauveau, P.; Delahaye, P.; Frigot, R.; Hormigos, S.; Jardin, P.; Thomas, J.C.; Tarvainen, O.
Abstract: The charge breeder of the SPIRAL1 (SP1CB) facility provided this year to physicists new Radioactive Ion Beams (RIB) for experiments and machine development, showing significantly improved performances compared to those obtained during the initial on-line commissioning of the SPIRAL 1 upgraded facility [1]. These improved performances were obtained thanks to thorough studies conducted off-line with 1+ ion beams produced by FEBIAD and ECR ion sources, successfully demonstrating the ability to couple SP1CB with them. In particular, the SP1CB established its capability to efficiently boost condensable elements such as 19 F n+, 32 S n+ and 54 Fe n+, in addition to more standard alkali elements. The charge breeding efficiencies have been investigated varying several parameters: buffer gas, beam transverse emittances. The ΔV curves of stable elements as well as radioactive ones were recorded for high charge states. Their trends are discussed in more detail. Finally, as molecular beams provide some advantages compared to atomic ion beams for selecting isobaric species and optimizing transport of the radioactive elements from the hot production target to the SP1CB plasma, we discuss if the charge-breeding efficiencies could also take advantage of beams in the molecular form. The performances of the 1+/N+ charge-breeding process were investigated using SF6 molecules broken into SFx 1+ ions and compared to regular F 1+ and S 1+ ions. This contribution will deal with these topics and latest results will be showed.